О возможном предназначении четырех деревянных рельефов XVI века из церкви Сан Николо в Падуе - Дроздова, Ульяна Олеговна (Актуальные проблемы теории и истории искусства, 2025)
Among art pieces in a little Paduan parish church of San Nicolò one series is of particular interest: four wooden bas-reliefs that represent the deeds of Christian saints (St. Bernardine Healing a King, Stigmatization of St. Francis, St. John the Baptist Preaching, and Bilocation of St. Anthony of Padua). The formal identity (vertical panels in narrow frames, measuring 1.88×1.32 m) and rhetorical unity of the reliefs (miracles of the saints who imitated Christ’s life, especially Franciscans) suggest they were once part of the same monumental decoration. According to church’s inventory books and pastoral visitation records, the panels were offered to the Cappella della Madonna by Girolamo dei Roberti in the early 17th century. In the article, it is identified with the third chapel in the right nave, which belonged to the Paduan Scuola della Carità, linked to the hospital and the Basilica of San Francesco Grande. It is just next to this basilica where woodcarvers Marcantonio and Agostino Vanini from Bassano live — basing on the published record in one of the inventory books concerning the reliefs, I re-attribute them to these sculptors. Finally, the function of the pieces in question may be defined by means of their comparison with two monumental projects with wood carvings that were made up in the second half of the 16th century in the Veneto region: choir stalls decoration in Santa Giustina in Padua and in San Giorgio Maggiore in Venice. Treating the four reliefs from San Nicolò as a part of a minor decoration adjusted to the needs of a little parish church allows us to ascribe them to a particular tradition of monumental wooden carvings that seem to have flourished in Northern Italy at the turn of the 17th century.
Keywords: монументальная деревянная резьба; декорация хоров; Ванини; скульптура Венето; скульптура Позднего Возрождения